If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2n + -4) = -72 Reorder the terms: 6(-4 + 2n) = -72 (-4 * 6 + 2n * 6) = -72 (-24 + 12n) = -72 Solving -24 + 12n = -72 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 12n = -72 + 24 Combine like terms: -24 + 24 = 0 0 + 12n = -72 + 24 12n = -72 + 24 Combine like terms: -72 + 24 = -48 12n = -48 Divide each side by '12'. n = -4 Simplifying n = -4
| 38.6+y=54.3 | | 5(3+6x)=285 | | 0.1x-2=11 | | 0.35x+0.35y= | | 2(x+3)=2x+12-6 | | 3r^2-9r+6= | | 19+15j+1=-19+6(4j-19) | | -16h+-1=15 | | -30=5b | | 4a+16+9= | | -4(4p+2)=-72 | | 5x+5=12.5 | | .5x+7=3x-8 | | -2(p-9)=0 | | 5*x*5=125 | | 0.20y-0.20x= | | -80=4(-6n+4) | | 30-14*2+8= | | 8(-z-18)+8z=-4-14z | | 3x+5x+4+-4-x+7=88 | | 7(x+4)-(8x+3)=5(2x-1) | | 3z=96 | | 2(x+6)=3x-3 | | 17+3b=26 | | 20y+-16y-2=6 | | 0.08y-8.05x= | | 4(-5k-4)=-76 | | 5-5n+2n=23-84 | | x+24+25x-6=70 | | -5(17+3u)=2(20-10u) | | 4(r+2)=20 | | 12m=93 |